2017
DOI: 10.7153/oam-2017-11-60
|View full text |Cite
|
Sign up to set email alerts
|

A spectral characterization of absolutely norming operators on S. N. ideals

Abstract: Abstract. The class of absolutely norming operators on complex Hilbert spaces of arbitrary dimensions was introduced in [6] and a spectral characterization theorem for these operators was established in [11]. In this paper we extend the concept of absolutely norming operators to various symmetric norms. We establish a few spectral characterization theorems for operators on complex Hilbert spaces that are absolutely norming with respect to various symmetric norms. It is also shown that for many symmetric norms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Let Π denote the set of all strictly decreasing convergent sequence of positive numbers with their first term equal to 1 and positive limit, that is, Π = {π := (π n ) n∈N : π 1 = 1, lim n π n > 0, and π k > π k+1 for each k ∈ N}. (We have used Π, in [8], to denote the set of all nonincreasing sequences of positive numbers with their first term equal to 1, and hence, in accordance with that notation, we have Π ⊆ Π.) For each π ∈ Π, let Φ π denote the symmetrically norming function defined by Φ π (ξ 1 , ξ 2 , ...) = j π j ξ j and observe that Φ π is equivalent to the maximal s.n.…”
Section: Proposition 33 Let φ Be An Sn Function Equivalent To the Max...mentioning
confidence: 99%
See 3 more Smart Citations
“…Let Π denote the set of all strictly decreasing convergent sequence of positive numbers with their first term equal to 1 and positive limit, that is, Π = {π := (π n ) n∈N : π 1 = 1, lim n π n > 0, and π k > π k+1 for each k ∈ N}. (We have used Π, in [8], to denote the set of all nonincreasing sequences of positive numbers with their first term equal to 1, and hence, in accordance with that notation, we have Π ⊆ Π.) For each π ∈ Π, let Φ π denote the symmetrically norming function defined by Φ π (ξ 1 , ξ 2 , ...) = j π j ξ j and observe that Φ π is equivalent to the maximal s.n.…”
Section: Proposition 33 Let φ Be An Sn Function Equivalent To the Max...mentioning
confidence: 99%
“…In [8], we used the theory of symmetrically normed ideals to extend the concept of "norming" and "absoutely norming" from the operator norm to arbitrary symmetric norms that are equivalent to the operator norm, and established a few spectral characterization theorems for operators in B(H) that are absolutely norming with respect to various symmetric norms. It was also shown that for a large family of symmetric norms the absolutely norming operators have the same spectral characterization as proven earlier for the class of operators that are absolutely norming with respect to the usual operator norm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also worth to point out that compact operators are always norm attaining. While the norm attaining property at the Banach space level has been studied extensively (for instance, see [1,12,13]), the same for operators on Hilbert spaces has so far received far less attention (however, see [7,14,15,16]). On the other hand, in 1965 Brown and Douglas [6, Lemma 2], in answering a question of H. Helson [11, page 12], established a close connection between arithmetic of inner functions, Toeplitz operators, and norm attaining operators on Hilbert spaces.…”
Section: Introductionmentioning
confidence: 99%